Delovanje Slovencev v Osijeku med drugo svetovno vojno - Riman, Barbara (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2016)
During WWII about 10,000 Slovenes were deported to the territory of the Independent State of Croatia, especially to localities remote from the present Slovene-Croatian border. In the places where they were settled, deportees soon made contact with the Slovenes that had already lived there. The present article highlights the nature of these contacts in Osijek in the interwar period, the importance of the cultural and artistic association that was founded in 1938, and how it evolved into the meeting place of the deportees. The paper also highlights the role of Ferdo Delak, an artist who actively participated in illegal actions, organized yje Slovene people and initiated the founding of town committees of the Liberation Front in the territory of Osijek.
Keywords: Osijek; Slovenci na Hrvaškem; izgnanci; druga svetovna vojna; World War II